Comparison of scoring systems and outcome of patients admitted to a liver intensive care unit of a tertiary referral centre with severe variceal bleeding. Issue 11 (16th April 2014) - Al‐Freah, M. A. B.; Gera, A.; Martini, S.; McPhail, M. J. W.; Devlin, J.; Harrison, P. M.; Shawcross, D.; Abeles, R. D.; Taylor, N. J.; Auzinger, G.; Bernal, W.; Heneghan, M. A.; et al.
Summary Background Acute variceal haemorrhage (AVH) is associated with significant mortality. Aims To determine outcome and factors associated with hospital mortality (HM) in patients with AVH admitted to intensive care unit (ICU) and to compare outcomes of patients requiring transfer to a tertiary ICU (transfer group, TG) to a local in‐patient group (LG). Methods A retrospective study of all adult patients (N = 177) admitted to ICU with AVH from 2000–2008 was performed. Results Median age was 48 years (16–80). Male represented 58%. Median MELD score was 16 (6–39), SOFA score was 8 (6–11). HM was higher in patients who had severe liver disease or critical illness measured by MELD, SOFA, APACHE II scores and number of failed organs (NFO), P < 0.05. Patients with day‐1 lactate ≥ 2 mmol/L had increased HM (P < 0.001). MELD score performed as well as APACHE II, SOFA and NFO (P < 0.001) in predicting HM (AUROC = 0.84, 0.81, 0.79 and 0.82, respectively P > 0.05 for pair wise comparisons). Re‐bleeding was associated with increased HM (56.9% vs. 31.6%, P = 0.002). The TG (n = 124) had less severe liver disease and critical illness and consequently had lower HM than local patients (32% vs. 57%, P = 0.002). TG patients with ≥2 endoscopies prior to transfer had increased 6‐week mortality (P = 0.03). Time from bleeding to transfer ≥3 days was associated with re‐bleeding (OR = 2.290, P = 0.043). Conclusions MELD score was comparable to ICU prognostic models in predicting mortality. Blood lactate was also predictive of hospital mortality. Delays in referrals and repeated endoscopy were associated with increased re‐bleeding and mortality in this group.